Prevalence of disability in Morocco: Results from a large-scale national survey - Abderrazak Hajjioui; Naïma Abda; Rachid Guenouni; Chakib Nejjari; Maryam Fourtassi (Medical Journals Sweden, 2019)
Objective: Disability is considered a global health problem, with an increasing number of persons with disabilities. Up-to-date and good-quality data on disability are essential to policymakers in order to establish tailored programmes for persons with disabilities based on the specific needs of each category. The aims of this study were to determine the prevalence of disability in the adult Moroccan population, and its distribution according to socio-demographic characteristics and geographical regions. Methods: A national survey was conducted in 2014, including a sample of 47,275 adult participants drawn from 16,044 households from urban and rural areas proportioned to population size. The sample's socio-demographic characteristics were collected in face-to-face interviews. The data were then screened for disability using the Washington Group Short Set of Questions on Disability. Results: Overall prevalence of disability among the Moroccan adult population was 9.5%, with important geographical disparities. Older age, lower education rates, unemployment, being single, and living in rural areas, were associated with higher prevalence rates of disability. Visual and motor deficiencies were the most common disability modalities, and the prevalence of moderate-to-extreme disability, which is associated with more significant limitations in functioning, was 2.6%. Discussion/Conclusion: Results from this national Survey are critical and would guide national disability policies and programmes, in order to reduce disabling barriers and improve persons with disabilities access to healthcare and participation.